Oncogene mutational analysis in imatinib naive population of gastrointestinal stromal tumor patients - Ali Abuderman, Abdul Wahab; M. Aldakheel, Fahad (Cellular and Molecular Biology, 2020)
There are very scanty reports on gastro-intestinal stromal tumors (GISTs), a very common tumor of mesenchymal cells in GIT track primary resistance to imatinib. This comprehensive study identifies the prevalence, clinical presentation and GIST genotype association in the imatinib naí¯ve population. Prospectively a record of anthropometric, baseline demographic data and clinical details for the patients diagnosed with GIST were scrutinized. Pathological information included the presence or absence of necrosis, tumor size, mitotic counts, immune-histochemical staining for CD 34, CD 117 and DOG1 was performed using biopsy sample. Selected exon genes of KIT, PDGFRA and BRAF were amplified and subjected to mutation analysis by direct sequencing. Appropriate statistical analyses were performed. The male/female ratio was 1.8:1 among 54 patients with GIST. The mean GIST size was comparatively bigger in females (2.49±0.855) than males (2.26±1.13). The stomach was the most common site for GIST followed by the Small bowel and rectum. The majority of the tumours were spindle cell. This study reports 12 different types of mutation among 39 KIT, 8 PDGFRA and 7 BRAF mutations. In KIT, the most prevalent was exon 11 mutation with the KITdelinc557/558 (14/30) being the major exon 11 type mutation. In PDGRFA, five exons 18 with p.D842V substitution and three exons 12 deletion mutation was reported. Seven patients had strong or diffuse BRAF staining having V600E type mutation as major BRAF type mutation. Drug-resistant GIST due to acquired mutations remains a serious issue, therefore genetic information of such mutational related to drug-resistant may provide the imperative clue for diagnosis and clinical treatment. These mutations are pivotal for prognosis and associated with imatinib as not all of them but only a few are reported resistant to the imatinib.